Bogdan Raditsa, the 1970s and the Question of Croatian Emigration - Šesnić, Jelena (2014)
The article contends against a fallacious assumption that Croatian political emigration in the second half of the twentieth century formed a homogeneous and monolithic whole, while it is rather the case that it was fissured and destabilized by each successive wave of emigrants. This differentiation is here presented in a number of contributions by Bogdan Raditsa, written in the 1970s and published in Hrvatska revija predominantly and occasionally in other emigration journals as well. Raditsa, as one of the nestors of the “new emigration” occurring after World War Two, notes a trend of increasing radicalization of the emigrants entering political arena as a result of reprisals following the suppression of the Croatian Spring in 1971. The 1970s are thus seen as a pivotal decade in which generational distinctions within Croatian emigration were manifested in a number of high-profile radical and terrorist acts committed by the latest wave of emigrants. Raditsa’s position indicates his adherence to democracy and liberalism on the model of the United States, while he subjects different models of political activism in emigration to reasoned scrutiny. His political analysis is not only a record of a diasporic intellectual disposition but also an incisive comment on the vicissitudes of Croatian politics in the stifling embrace of the Cold War. Consequently, an argument is forwarded that calls for a definitive inclusion of political diaspora into Croatian Cold-War history, while suggesting that such a goal might be achieved among other things by a sustained reception of Raditsa’s formidable oeuvre.
Keywords: Bogdan Raditsa; Croatian emigration; the Croatian Spring; the 1970s; terrorism